2006
DOI: 10.1111/j.1365-2141.2006.06076.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase deficiency in France: a 3‐year study reveals 27 new mutations

Abstract: Summary Pyruvate kinase (PK) deficiency is the most common enzyme defect affecting the glycolytic pathway of the erythrocyte. Usually, it is clinically silent in heterozygotes but serious disorders are described at birth in homozygotes or compound heterozygotes. Including the mutants herein reported, more than 180 mutations of the PK‐LR gene have now been identified. This 3‐year study was carried out to detect mutations associated with disease‐affecting families. Haematological indices, erythrocyte PK and gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…Amino acid substitutions in the B domain are rare and only seven mutations have been described thus far Kugler et al, 2000;Neubauer et al, 1991;Pissard et al, 2006;Zanella et al, 1997]. The side chain of Arg163 points into the cleft between the A and B domains where the active site is located.…”
Section: The Novel Pgly111arg Pk Variant Is Prevalent In the Dutch Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid substitutions in the B domain are rare and only seven mutations have been described thus far Kugler et al, 2000;Neubauer et al, 1991;Pissard et al, 2006;Zanella et al, 1997]. The side chain of Arg163 points into the cleft between the A and B domains where the active site is located.…”
Section: The Novel Pgly111arg Pk Variant Is Prevalent In the Dutch Pmentioning
confidence: 99%
“…Pissard et al [2006Pissard et al [ , 2007 recently reported the c.375110G4T change to be associated with PK deficiency, either on itself or in cis with missense mutations c.1178A4G (p.Asn393Ser) and c.359C4T (p.Ser120Phe). They did not detect the c.375110G4T change in their normal controls (n 5 100).…”
Section: The Novel Pgly111arg Pk Variant Is Prevalent In the Dutch Pmentioning
confidence: 99%
“…Subsequent population studies have increased this total by over 44 novel mutations [18,44]. Mutations are found in every exon, as well as several introns, all of which result in human PK deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Two mutations, both located in exon 11, are recurrent (Arg510 → Gln, Arg486 → Trp). Arg510→ Gln is the most frequent mutation found in northern Europe, central Europe and the USA (Pissard S. at al., 2006, as citated Wang et al, 2001) and Arg486 → Trp in southern Europe (Spain, Portugal and Italy) and in France (Pissard et al, 2006, as citited Zanella et al, 1997Zarza et al, 1998;Pissard et al, 2006). The most frequent mutations of PKLR gene in the Indian population appear to be 1436G→A (19.44%), followed by 1456C→T (16.66%) and 992A→G (16.66%) (Kedar et al, 2009).…”
Section: Point Mutation In Pyruvate Kinasementioning
confidence: 99%